2022
DOI: 10.47895/amp.v56i1.3937
|View full text |Cite
|
Sign up to set email alerts
|

Discoursing Terminology Standards and Interoperability in relation to the Philippine eHealth Strategy

Abstract: Background. eHealth is the use of information and communication technologies (ICT) for health. It helps in improving the flow of information, through electronic means, in support of the delivery of health services, and the management of health systems. eHealth is used as the strategic context and tool in achieving population health, improved health system status, and socio-economic development goals. Objectives. This study is aimed at looking at the Philippine National eHealth Strategy, particularly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Indeed, interoperability, which should facilitate easier data transfer across health facilities is still a strategic challenge for the government and other key sectors. 8 The pandemic has also affected the EMR interactions of RHUs differently and may have further delayed progress in adoption of some users. Based on the Taiwan experience, where interinstitution exchange following EMR implementation took ten years, a strong incentive mechanism must be present for successful digitization of healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, interoperability, which should facilitate easier data transfer across health facilities is still a strategic challenge for the government and other key sectors. 8 The pandemic has also affected the EMR interactions of RHUs differently and may have further delayed progress in adoption of some users. Based on the Taiwan experience, where interinstitution exchange following EMR implementation took ten years, a strong incentive mechanism must be present for successful digitization of healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…On the EMR output process, the review reported variability on ICT interventions, standardization, and interface issues. 12 Based on the findings of the said review 12 as well as the factors identified as drivers of the eHealth strategy in the Philippines 7,8 , an IPO (input-process-output) framework 13 , commonly used in organizational behavior research, was adopted for this study (Figure 2). The model posits that adoption or use of EMR requires several direct inputs from the environment to produce the identified outputs.…”
Section: Emr Adoption and Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, physicians recognize that higher remuneration in the private sector is an incentive. However, they believe that they could be more dedicated to the sector and committed to a specific health group if there was a more attractive material and non-material incentive policy that valued the professionals and made a difference in the choice of the health group itself [45,46] . The structuring of the incentive system was mentioned in the various interviews, where physicians suggested being involved.…”
Section: Discussionmentioning
confidence: 99%